The Function of Art in the Frankfurt School’s Vision - Seghiri, Racha Wissal; Mefaredj, djamel (Journal of Human Sciences, 2023)
Research on the subject of the function of art in general is of great importance today, and is particularly important in the flags of the first generation of the Frankfurt School, which was characterized by its critical thinking of the enlightenment project, which formed the basic basis of Western modernity. This school sought to free the European mind from the performing mind and restore the human humanity, and art was its bet, so we raise the following problem: can art play its critical and liberal role in the enormous technological advances that contemporary industrial societies have known in the perspective of the Frankfurt School?  Through our research, we have found that the evidence of art has hindered him from playing the role assigned to him by the Frankfurt School, due to the entertainment of art and its exploitation in advertising and propaganda to serve ideology and political purposes.